An Integrated Population Pharmacokinetic Meta‐Analysis of Propofol in Morbidly Obese and Nonobese Adults, Adolescents, and Children. (11th September 2013) - Diepstraten, J; Chidambaran, V; Sadhasivam, S; Blussé van Oud‐Alblas, HJ; Inge, T; van Ramshorst, B; van Dongen, EPA; Vinks, AA; Knibbe, CAJ
Abstract : This study describes a population pharmacokinetic meta‐analysis of propofol to characterize the influence of body size measures and age in morbidly obese and nonobese adults, adolescents, and children. Sixty morbidly obese and nonobese adult patients (55–167 kg; 21–79 years) and 34 morbidly obese and nonobese adolescents and children (37–184 kg; 9–20 years) were included. The results show that clearance increased with total body weight in an allometric function while age was found to influence clearance in a bilinear fashion with two distinct slopes, reflecting an initial increase and subsequent decrease as a result of aging. Using these two functions, the influence of both (over)weight and age on propofol clearance was well characterized, which may provide a basis for dosing across this diverse group of patients. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e73; doi:10.1038/psp.2013.47 ; advance online publication 11 September 2013